Vascular endothelial growth factor is elevated in ocular fluids of eyes harbouring uveal melanoma: identification of a potential therapeutic window. Issue 4 (1st April 2002) - Boyd, S R; Tan, D; Bunce, C; Gittos, A; Neale, M H; Hungerford, J L; Charnock-Jones, S; Cree, I A
Abstract : Background: Improved local treatment of uveal melanoma makes it possible for many patients to retain the affected eye, but a proportion will develop secondary complications such as neovascularisation of the iris (NVI) and require enucleation. Although vascular endothelial growth factor A (VEGF-A) is known to correlate with NVI and can cause NVI in experimental models, this pro-angiogenic cytokine is consistently reported to be absent in uveal melanoma. Novel anti-VEGF therapies are now in clinical trial, and the authors therefore wished to determine whether VEGF-A was indeed elevated in melanoma bearing eyes. Methods: VEGF-A concentrations were measured in aqueous and vitreous from 19 and 30 enucleated eyes respectively. Results: Elevated VEGF-A concentrations (up to 21.6 ng/ml) were found in melanoma bearing eyes compared with samples from patients undergoing routine cataract extraction (all had values below 0.96 ng/ml). Immunohistochemistry showed VEGF-A protein in the iris and/or ciliary body of 54% and basic fibroblast growth factor (bFGF) in 82% of the eyes examined. VEGF was found to a limited extent and at very low levels in only 9% of these tumours. Aqueous or vitreous VEGF levels showed no apparent correlation with retinal detachment, tumour size, vascularity, or immunohistochemistry. Though limited in number, the highest VEGF levels correlated with previous radiation therapy, and with the presence neovascularisation of the iris or optic nerve head. bFGF was not significantly elevated in ocular fluids: it is known to be a pro-angiogenic agent and was detected in the majority of primary uveal melanomas. Conclusion: Based on this study, though the source of VEGF within eyes harbouring uveal melanoma is not clear, these data suggest that anti-VEGF therapy might prove useful in the management of some patients with NVI secondary to uveal melanoma.